Thermal environment characterization for the bovine cattle ranching in the Valle del Cauca, Colombia - Raúl Andres Molina Benavides; Fernando Silva Aguilar; Sandra Milena Perilla Duque; Hugo Sánchez Guerrero (Acta Agronómica)
The influence of climate on animal behavior has been demonstrated for many years. Climatic variables such as temperature (T, ° C), relative humidity (RH, %), solar radiation (SR, W / m2) and wind speed (WS, m / s), outside their normal range, can displace ruminants of their comfort zone, which can results in negative impact on their productivity and reproduction behavior. In order to characterize the thermal environment of bovine cattle ranching in the Valle del Cauca department, two biometeorological indexes (heat load index for dairy cows and meat cattle) were performed to develop an animal - environment relationship. The indexes were applied to the most representative Valle del Cauca department climatic ranges (T = 20-35; RH = 60-100; WS = 0-10), finding that for dairy cows under the mentioned conditions of T> 23, RH> 80 and 0 WS, starting to show signals of heat stress, while for beef cattle starts with T> 25, RH> 60 and WS <1.5. In conclusion, these indexes are useful tools to determine the degree of heat stress that may occur on farms during certain times of day for certain months of the year, helping to plan actions to control its effect in cattle and subsequently, mitigate the impacts on their productive and reproductive performance.